Investigation into the Promotion and Motivation Instruments of Medical Staff in Lithuania’s Regional Healthcare Institutions - Juodišiūtė, Živilė; Vorevičienė, Jurgita (Jaunųjų mokslininkų darbai, 2016)
Personnel is one of the most important resources, sensitive to social and economic changes that affect the state or organisation. Therefore personnel management methods should be most advanced and oriented to a person rather than a technical worker. Moreover, the institution should foster cooperation and build trust among its employees and administration, set such goals that address its objectives and individual needs. Regional healthcare institutions in Lithuania need qualified, innovative and talented staff. Newly qualified healthcare professionals are unwilling to work in those institutions not only because they are located in regions but also because used personnel management methods are outdated, employee initiatives to cooperate are not supported, some employee groups are favoured, other groups are paid less. The paper analyzes methods that healthcare institutions use to promote and motivate their medical staff, to build good relationships between the administrative and medical staff. Some assumptions why vacancies are not filled in these institutions are provided. It was found that managers and leaders of some healthcare institutions do not know how to motivate staff, often use outdated employee promotion methods from Soviet times, take no account of individual needs.